GAMBARAN KADAR UREUM KREATININ PADA PENDERITA DIABETES TIPE-2 DI RUMAH SAKIT OTIKA MEDIKA SERANG BANTEN - Melani MS, Ela; Anggita Kartikasari, Ledy (Jurnal Infokes, 2021)
The relationship between urea and creatinine with diabetes mellitus sufferers, where diabetes mellitus has high blood levels (hyperglycemia), this condition causes the walls of blood vessels to be damaged, resulting in blockages that cause microvascular complications, one of which is diabetic nephropathy. This research was conducted using descriptive method which aims to determine the percentage increase in urea levels in type 2 Diabetes Mellitus patients who are hospitalized at Otika Medika Hospital Serang. The research sample consisted of 31 samples of Diabetes Mellitus type 2 patients who were hospitalized and outpatient at the Otika Medika Hospital Serang in June and July 2020. The examination method used was based on the spectrophotometer method. And this research was carried out in the hospital clinical laboratory installation Otika Serang. The results of the research that have been done found that patients with normal uerum levels were 48.3%, urea levels increased by 51.6%. While normal creatinine levels were found to be 29%, and patients with increased creatinine levels were found to be 70.1%. The test results based on age of urea and creatinine levels were dominated by patients aged 46-65 years, found 32.2% with normal urea levels, and 32.2% with increased urea levels. Creatnine levels were found to be 16.1% with normal creatinine levels, and 48.3% with elevated creatinine levels. The test results were based on gender, it was found that normal urea levels were mostly found in male patients amounting to 26%. And increased urea levels were found in female patients amounting to 35%. Normal creatinine levels were mostly found in male patients amounting to 22%. And increased urea levels were found in female patients amounting to 52%.